Employment protection and parental child care - Martin Olsson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
I examine if employment protection affects parental childcare. I find that a softer employment protection has a substantial effect on how parents use and divide paid childcare between them. The identification relies on a reform that made it easier for employers in Sweden to dismiss workers in small firms. I estimate that a softer employment protection reduces the total days of parental childcare in targeted firms, measured as total days of parental leave or temporary parental leave. Both a sorting effect and a behavioral effect can explain the reduced childcare. I also find evidence of a redistribution effect of paid parental childcare within households if only one partner was affected by the reform. I interpret the redistribution effect as a way of evading an external cost on the child.
Keywords: J13; K13; 330; employment protection; parental childcare; within family distribution; Kündigungsschutz; Kinderbetreuung; Familienökonomik; Wirkungsanalyse; KMU; Schweden